2016
DOI: 10.29210/17000
|View full text |Cite
|
Sign up to set email alerts
|

Profil Perilaku Agresif Siswa dan Implikasinya bagi Bimbingan Konseling

Abstract: Aggressive behavior is an act of violence that harm, hurt, injure because it will harm the victim that was done on purpose in the form of active or passive, physically or verbally either in person or not. The purpose of this study was to determine the profile of aggressive behavior class XI SMA Laboratorium UM Malang. The method used in this research is descriptive analysis. The results showed that (1) the level of aggressive behavior in class XI SMA Laboratorium UM Malang high, (2) the level of aggressive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The results of this study are consistent with Sari's (2016) study which revealed that the level of aggressive behavior of students was generally classified as high and there were differences in aggressive behavior based on gender (Sari, 2016). Furthermore, some physically aggressive behavior shows direct anger (hitting, kicking, pushing while insulting).…”
Section: Data Description Level Of Aggressive Behavior Of Female Studsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are consistent with Sari's (2016) study which revealed that the level of aggressive behavior of students was generally classified as high and there were differences in aggressive behavior based on gender (Sari, 2016). Furthermore, some physically aggressive behavior shows direct anger (hitting, kicking, pushing while insulting).…”
Section: Data Description Level Of Aggressive Behavior Of Female Studsupporting
confidence: 90%
“…Research by Guswani & Kawuryan (2011) revealed that the level of aggressive behavior of 13 people (8.67%) was in the very high category; high 33 people (22%); while 51 people (34%); low 48 people (32%), and very low 5 people (3.33%). Furthermore, Sari's research (2016) revealed that the level of students' aggressive behavior was generally high and there were differences in aggressive behavior based on gender (Sari, 2016). The Indonesian Child Protection Commission (KPAI) currently records 1,000 cases of violence in 2016 (Sugiarto, 2017).…”
Section: Introductionmentioning
confidence: 99%